Using digital reading in ESL Malaysian primary classrooms: the strengths and the shortcomings from the learners’ perspectives - Nurul Qistina Baharuddin; Harwati Hashim (Global Econedu, 2020)
This paper discusses the relevance of digital reading in Malaysian education setting, especially in second language acquisition. This paper provides some definitions on digital reading before further elaborates the underlying theoretical framework, TAM model (1989). Later on, the strengths and the shortcomings of digital reading are presented to provide adequate information on the research topic. 30 Level 2 pupils from a primary school in a state in Malaysia had participated in the survey and ten of them were randomly selected for the interview session. This research found that ESL primary learners enjoy digital reading as it is useful and interesting to be explored in their language learning. Despite the existing limitation due to lack of related facilities at school, digital reading seems to be a convincing approach for ESL learners in language mastery. It is hoped that this paper initiates more research in the area of topic for future global benefits.